Minding the Gap: Using Implementation Science to Improve Clinical Practice in Schools. - Komesidou, Rouzana; Hogan, Tiffany P. (Language, Speech & Hearing Services in Schools, 2023)
Purpose: This purpose of this prologue is to introduce readers to the Language, Speech, and Hearing Services in Schools Forum: Minding the Gap: Using Implementation Science to Improve Clinical Practice in Schools. Ten articles comprise this forum presenting a variety of topics, such as the use of implementation science frameworks and methods, program adaptation, de-implementation, and interprofessional collaboration. Conclusion: As showcased in this forum, implementation science offers many ways to bridge the gap between research and practice and improve schoolbased services for children with communication disorders.